A fool for a client [large type] - Hall, Parnell (Hall, Parnell. Stanley Hastings mystery novel., 2016)
A young woman is found naked and stabbed to death -- it's the type of case that should be perfect for Stanley Hastings. Instead, it's his nightmare. The woman was the girlfriend of his boss, Richard Rosenberg, and the hotshot lawyer is charged with killing her.